Jīwana Paṃ. Jawāhara Lāla Nahirū - Sītala, Dhanawanta Siṅgha (SAMP early 20th-century Indian books project, 1952)
Biography of Jawaharlal Nehru, 1889-1964, first prime minister of India; for children.